Polimorfismo molecular em populações de Tetragonisca angustula Latreille (Apidae ; Trigonini) - Baitala, Tatiane Vicente (2005)
Molecular Polymorphism in Populations of the Tetragonisca angustula Latreille (Apidae; Trigonini). Tetragonisca angustula is one of the commonest neo-tropical stingless bees and an important pollinator agent. For this project, RAPD markers were used in order to estimate the genetic structure of five populations (14 colonies) of the Tetragonisca angustula bees. Twelve primers that reproduced 171 fragments, of which 150 were polymorphic (87.72%), were used. The estimate of gene diversity with the Shannon?s index was of 0.3929 (± 0.2329). The gene flow (Nm) was of 1.4474 and the GST value was of 0.2568. Isolation was verified along with the values of the genetic distance among the populations from the Northwest of Paraná state (Maringá and Cianorte) and from the São Paulo state (Junqueirópolis). Six markers that differentiated the populations of the T. angustula from the São Paulo state and Paraná state, were identified; however those markers were not able to separate the subspecies T. a. angustula and T. a. fiebrigi.